Iron leaching from nonrefractory grade bauxite: Individual process optimization and prediction by using DOE. Issue 2 (15th January 2022) - Stein, Alena; Sax, Almuth; Quirmbach, Peter
Abstract: Bauxite is an important raw material for the production of refractories. The availability of refractory grade ore worldwide is limited, and high iron contents in particular reduce the quality of the material. For refractory applications, a maximum iron content of 2 % is acceptable. In this study, acid leaching with HCl is used to decrease the iron content in different nonrefractory grade raw bauxites. Computerized design of experiments and statistical methods are used to determine optimum process parameters and influencing factors for different bauxites individually. Compared to previously published studies, the applied approach makes it possible to process even very iron‐rich bauxites (e.g., 31 % Fe2 O3 in calcined substance) and to lower their Fe2 O3 contents below the permitted 2 %. In addition, larger grain sizes (around 5.5 mm) can be used. Statistical planning and mathematical modeling also allow the prediction of the minimum achievable iron content within the investigated parameter ranges. For selected parameter combinations, the achievable Fe2 O3 content can be predicted relatively accurately without the requirement for practical testing of the corresponding experimental setup.